71‐3: Static Laser Phosphor for Projectors with Rotating Tilted Mirror. Issue 1 (28th June 2022) - Li, Kenneth; Chang, Y.P.; Wang, Lion; Chen, Andy; Cheng, W.H.; Han, Pin; Chen, Chih-Ming; Liu, C.N.
Abstract : Laser excited phosphor has much higher brightness than that of LEDs and are suitable for many high power, low etendue applications. One of the major obstacles is heat sinking of the phosphor in high power applications with the phosphor material coated onto a rotating wheel. This paper presents a static phosphor plate system in which the phosphor plate is stationary and can be attached to traditional heat sinks for efficient removal of heat at high power, which cannot be achieved easily when the phosphor material is on a rotating wheel. The highest equivalent power density of estimated from 300 W to 600 W per sq. mm has been achieved, which is over 6 times higher than the original limit of the phosphor material. It is also found that the thickness of the phosphor plays an important role in the power density limits. Thinner phosphor plates are being investigated for even higher power operations with expected high limits.